Ibuprofen Dependence: A Case Report - Etcheverrigaray, F.; Grall-Bronnec, M.; Blanchet, M.-C.; Jolliet, P.; Victorri-Vigneau, C. (Pharmacopsychiatry, 2014)
Ibuprofen is currently widely prescribed and has not been reported to produce dependence. We report the case of a 17-year old patient who presented many positive psychics symptoms related to a pharmacological dependence. During the treatment, she adjusted herself posology as she developed withdrawal symptoms. Pharmacological evidences (effect on COX-1 and COX-2, FAAH and PPARs) allow us to formulate hypotheses explaining this effect.
Keywords: ibuprofen; dependence; cannabinoid receptor modulators; peroxisome proliferator-activated